THE IMPORTANCE OF HUMOR IN FORMING A PERSON'S DEMOCRATIC THINKING (Conferencea, 2025)
In the article, the importance of humor in the formation of a person's democratic thinking, as well as comic works can make people laugh and cry, so this process is an aesthetic phenomenon closely related to the social and cultural aesthetic feelings of a person.